MicroRNAs and response to therapy in leukemia. Issue 9 (12th May 2019) - Sharifi, Hossein; Jafari Najaf Abadi, Mohammad Hassan; Razi, Ebrahim; Mousavi, Nousin; Morovati, Hamid; Sarvizadeh, Mostafa; Taghizadeh, Mohsen
Abstract: A variety of epigenetic factors involved in leukemia pathogenesis. Among various epigenetic factors, microRNAs (miRNAs) have emerged as important players, which affect a sequence of cellular and molecular signaling pathways. Leukemia is known as progressive cancer, which is related to many health problems in the world. It has been shown that the destruction of the blood‐forming organs could lead to abnormal effects on the proliferation and development of leukocytes and their precursors. Despite many attempts for approved effective and powerful therapies for patients with leukemia, finding and developing new therapeutic approaches are required. One of the important aspects of leukemia therapy, identification of underlying cellular and molecular mechanisms involved in the pathogenesis of leukemia. Several miRNAs (ie, miR‐103, miR‐101, mit‐7, let‐7i, miR‐424, miR‐27a, and miR‐29c) and play major roles in response to therapy in patients with leukemia. miRNAs exert their effects by targeting a variety of targets, which are associated with response to therapy in patients with leukemia. It seems that more understanding about the roles of miRNAs in response to therapy in patients with leukemia could contribute to better treatment of patients with leukemia. Here, for the first time, we summarized various miRNAs, which are involved in response to therapy in the treatment patients with leukemia.